2021
DOI: 10.1021/acs.jmedchem.1c01075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amide Bioisosteres Leading to 1,2,3-Triazole Containing Compounds as GPR88 Agonists: Design, Synthesis, and Structure–Activity Relationship Studies

Abstract: The orphan receptor GPR88 has been implicated in a number of striatal-associated disorders, yet its endogenous ligand has not been discovered. We have previously reported that the amine functionality in the 2-AMPP-derived GPR88 agonists can be replaced with an amide (e.g., 4) without losing activity. Later, we have found that the amide can be replaced with a bioisosteric 1,3,4-oxadiazole with improved potency. Here, we report a further study of amide bioisosteric replacement with a variety of azoles containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 48 publications
(168 reference statements)
0
29
0
Order By: Relevance
“…After reaching a stable baseline of responding, mice received saline or RTI-13951-33 (30 mg/kg, ip) 30 min before the 4-h alcohol self-administration session, using a within-subjects design (Weeks 14 and 15, Figure 3A). Total locomotor activity in the operant chamber was identical for saline-and RTI-13951-33-treated mice, suggesting that the GPR88 agonist did not impair mouse activity under our conditions (t [18] = 0.92, p = 0.36) (Figure 3B).…”
Section: Rti-13951-33 Reduces Alcohol Selfadministrationmentioning
confidence: 79%
See 1 more Smart Citation
“…After reaching a stable baseline of responding, mice received saline or RTI-13951-33 (30 mg/kg, ip) 30 min before the 4-h alcohol self-administration session, using a within-subjects design (Weeks 14 and 15, Figure 3A). Total locomotor activity in the operant chamber was identical for saline-and RTI-13951-33-treated mice, suggesting that the GPR88 agonist did not impair mouse activity under our conditions (t [18] = 0.92, p = 0.36) (Figure 3B).…”
Section: Rti-13951-33 Reduces Alcohol Selfadministrationmentioning
confidence: 79%
“…13 We have pioneered the design, synthesis and study of a family of GPR88 agonists, starting from 2-PCCA 14,15 to novel series of brain-penetrant drugs with improved potency and efficacy. [16][17][18] In particular, RTI-13951-33, 16 the second-generation lead GPR88 agonist, shows nanomolar potency (EC 50 = 25 nM) at the recombinant receptor using an in vitro cAMP assay. Moreover, the compound efficiently stimulates GPR88-mediated G protein activity in striatal membranes prepared from control but not Gpr88 knockout mice, indicating activity and specificity at the native receptor.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the two conditional lines together recapitulate the impulsivity-related de cits observed in the germ line Gpr88 knockout mice, making unlikely the possibility that the constitutive mutant phenotype is entirely due to early developmental compensatory mechanisms. In the future, the novel pharmacological tools under development may de nitely answer this question 10,49,50 .…”
Section: Gpr88 Regulates Impulsive Behaviorsmentioning
confidence: 99%
“…Accurate SARs may be obtained by comprehensively comparing side chains without changing the scaffold, which is the central backbone of the original molecule. Some of the latest research to identify anticancer drugs, psychiatric drugs, , antivirus drugs, , and even antibody–drug conjugates , are based on SARs, which represent an indispensable important research method.…”
Section: Introductionmentioning
confidence: 99%